THE TRANSFORMATION OF DISCONTENT: REINTERPRETING “ANGRY YOUNG MEN” THEMES IN 21ST-CENTURY GLOBAL LITERATURE - Chinakov Abdulahad Muminjon ugli (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This extended thesis explores the evolution and reinterpretation of the mid-20th-century British "Angry Young Men" literary movement within the context of contemporary global literature. Originating in post-World War II Britain, the Angry Young Men articulated discontent with entrenched class systems, political stagnation, and the alienation of the working class. This paper examines how those foundational themes of rebellion, class conflict, and identity crisis are being revived and transformed in the 21st century by authors such as Mohsin Hamid[4], Aravind Adiga[2], Dave Eggers[3], and Ocean Vuong[6]. These modern voices adapt the core concerns of their predecessors to address global issues, including economic inequality, technological alienation, intersectional identity, and postcolonial realities. Through comparative literary analysis, the paper demonstrates how the discontent of the mid-20th century persists in reconfigured forms, resonating deeply with modern readers across diverse cultures.